Whistleblower, soldier, spy a journey into the dark heart of the global war on terror - Clonan, Tom 1968- (Liberties Press, 2013)
From Dublin to Beirut, Guantanamo Bay to Iraq - and all the way back - Tom Clonan takes the reader on a very personal journey through the Global War on Terror. The book deals with a variety of themes including death, mayhem and murder, loss of loved ones, fear of flying and the hazards of having four children and a dog!